Analysis and Theory in International Relations - A. D. Bogaturov (Сравнительная политика, 2020)
A new attempt to analyze the situation in the interaction of different countries gives another interpretation of the meaning of the behavior of states. The task is to arrange words containing their meaning and be prepared for situational analyzes. A new problem is the conduct of illusory analyzes and their relationship with the traditional ones, the difference between which lies in the online participation of participants and in comparison with their physical presence at the venue. The problem lies in identifying the difference and analyzing the merits and demerits of the both methods. Analysis is a quick, immediate analysis of the situation, theory is a way of reasoning with a stretch in time, ways of checking versions that can be conﬁrmed and become a theory. But it might not be conﬁrmed ‒ in this case, the analysis remains “postponed until new visits” by checking a similar situation. A careful selection prepares the analysis to be carried out given the security of states, depending on one scenario or another factors. Winter-spring 2020 witnessed the pandemic in the world, which heightened fears of the policies of the leading powers. This heightened the demand for situational analyzes ‒ virtual and real, raised the question of traditional preferences.